Quantum Mechanical Analysis of GaN Nanowire Transistor for High Voltage Applications - Neel Chatterjee; Sujata Pandey (Журнал нано- та електронної фізики)
The paper presents the quantum mechanical analysis of Gallium Nitride nanowire transistor. The effect of high k gate dielectric and different gate metals on the electrical characteristics of the device is studied. Nanowire width has been reduced to have a proper control on the device characteristics at reduced gate length. A high value of drain current is obtained at gate length of 10 nm and nanowire radius equal to 10 nm, is obtained. Also high voltage operation of the device upto 40 volts has been shown. A flatter transconductance curve is obtained which shows the linearity of the device. The results obtained are comparable with the experimental and simulated data reported in literature